Remapping the Constellation of Walter Benjamin’s Allegorical Method - Wong Jack (American, British and Canadian Studies Journal, 2015)
The now-longstanding academic revival of allegory, as well as its import as a perennial buzzword of contemporary art criticism, owes much to a group of essays published in the journal October in the early 1980s. Authors Craig Owens and Benjamin Buchloh, in turn, drew a bloodline to the ideas of allegory that occupied Walter Benjamin throughout his literary career. However, whereas Benjamin saw allegory as the expression of a radical, indeed messianic, view of political possibility, the October writers found in allegory a counter-paradigm against Modernism that would resist the latter's totalizing tendencies by pursing its own deconstructive fate of “lack of transcendence.” In the following essay, I trace the source of this discrepancy to the crucial theological underpinnings of Benjamin's concept of allegory, without which the allegorical forms - appropriation and montage - produce not miraculous flashes of unmediated recognition but the permanent impossibility of communication.